Strategi Pengembangan Pariwisata Halal Pantai Biru Kabupaten Bangkalan Dalam Meningkatkan Perekonomian Masyarakat Sekitar - Mira Silfiya; Rudi Hermawan; Adiyono Adiyono (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2023)
he background to this research is that there are quite big challenges in Telaga Biru Village, Tanjung Bumi District, Bangkalan Regency, related to the unavailability of job opportunities for the young generation after completing high school (SMA). This also has an impact on other community groups, such as housewives and people who do not have jobs. This research aims to understand and identify strategies for developing halal tourism in Blue Beach, Bangkalan Regency, as well as the role of this tourist attraction in improving the economy of the surrounding community. There are two main aspects that are the focus of this research, namely the halal tourism development strategy and the role of the Blue Beach tourist attraction in the local economy. The method used in this research is qualitative through observation and in-depth interviews as well as audio recording activities which were also carried out at the interview stage to obtain additional information that may not have been recorded in detail in the field notes. The research results show that the Blue Beach Halal Tourism is very worthy of development because it is supported by attractiveness, accessibility, facilities, image and fairly good pricing. The development of halal tourism plays an important role in developing the economy of Telaga Biru village. This can be seen from the emergence of various types of businesses at tourist attraction locations, infrastructure improvements, the opening of new job opportunities, and an increase in the income of local communities.